PENINGKATAN KAPASITAS MANAJEMEN USAHA MIKRO NELAYAN MELALUI PELATIHAN PENCATATAN KEUANGAN SEDERHANA DI DESA BOKORI, KABUPATEN KONAWE, SULAWESI TENGGARA - Hamid, Wahyuniati; Juharsah, Juharsah; Conny, Conny; Ningtyas, Ajeng Purwati; Mubaraq, Ahmad; Daswan, Lestari; Maulana, Rifki (Pusat Studi Ekonomi, Publikasi Ilmiah dan Pengembangan SDM, 2025)
This activity aims to enhance the managerial capacity of micro-scale fishing enterprises in Bokori Village, Konawe Regency, through training in simple financial recordkeeping. Limited understanding and lack of habit in maintaining financial records remain major obstacles in business management. The program employed a participatory approach combining a three-day face-to-face workshop with intensive post-training mentoring. The training adopted andragogical and experiential learning principles, emphasizing hands-on practice. Results showed a significant improvement in participants’ understanding of basic financial recording concepts. Fishermen began separating business and household finances, leading to greater efficiency and higher income. Success was supported by continuous mentoring via a WhatsApp group and involvement of community leaders. Main challenges included maintaining consistency in recording small transactions and generational differences in comprehension. The program demonstrates the effectiveness of a blended learning approach and highlights the importance of strengthening local institutions through cadre formation to ensure sustainability.